Composite material, preparation method and application thereof, and rubber

By introducing the modified inorganic filler surface coupling structure M and structure A1 into the rubber antioxidant, a composite material is formed, which solves the problems of the existing rubber antioxidants being easy to volatilize, migrate, have poor dispersion and extraction resistance, and achieves a better Good thermal oxidative aging strength and migration resistance.

CN119331310APending Publication Date: 2025-01-21CHINA PETROLEUM & CHEMICAL CORP +2
View PDF 7 Cites 0 Cited by

Patent Information

Application Number
CN202310895776.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2023-07-20
Publication Date
2025-01-21

AI Technical Summary

Technical Problem

Existing rubber anti-aging agents are easy to volatile, easily migrate, have poor dispersion in rubber, and have poor extraction resistance, resulting in aging and degradation of rubber properties.

Method used

By introducing the coupling structure M and the structure A1 shown in formula (1) on the surface of the modified inorganic filler, a composite material is formed and used as a rubber antioxidant. The composite material improves the thermal oxidative aging strength and migration resistance of the antioxidant through the combination of coupling structure M and structure A1.

Benefits of technology

It achieves better thermal oxidation aging strength, migration resistance and compatibility of rubber antioxidants, and has the medium and long-term protective properties of traditional antioxidants, as well as migration resistance.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119331310A_ABST
    Figure CN119331310A_ABST
Patent Text Reader

Abstract

The invention relates to the field of rubber anti-aging agents, and discloses a composite material, a preparation method and application thereof, and rubber. Wherein the composite material comprises a modified inorganic filler, and a structure A1 and # imgabs 0 # which are connected to the surface of the modified inorganic filler and are shown in a formula (1), R is selected from H or # imgabs 1 #, R1 is selected from H or C1-C6 alkyl, R'is selected from H, C1-C10 alkyl, # imgabs 2 # imgabs 3 #, R2 is selected from C1-C6 alkylene or C1-C6 alkylene ether, R3 is selected from C1-C6 alkylene, and R4 is selected from C1-C12 alkyl; r ''does not exist or is selected from C1-C20 oxygen-containing groups. The invention provides a composite material serving as an anti-aging agent in rubber, and the composite material serving as the rubber anti-aging agent has medium and long-term protection performance of a traditional anti-aging agent and also has the characteristic of migration resistance; the preparation method of the rubber anti-aging agent has the advantages of simple process, high product yield and the like; in addition, the rubber anti-aging agent has good dispersibility in rubber.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the field of rubber antioxidants, and in particular to a composite material, a preparation method and application thereof, and rubber. Background Art

[0002] Rubber materials are widely used in production and life due to their advantages of light weight, good flexibility, good sealing, and shock absorption and buffering. However, the unsaturated bonds in rubber materials can easily cause rubber aging, thus affecting the long-term use of rubber materials.

[0003] Rubber antioxidants are mainly divided into amine antioxidants, phenolic antioxidants, heterocyclic antioxidants and other categories, among which amine antioxidants are mostly small molecule compounds, such as IPPD, 6PPD, etc. Literature reports that the small molecule antioxidant 6PPD in automobile tires is easy to migrate out and will be further ozonated to form highly toxic substances, which has largely caused a sharp decline in the number of salmon populations.

[0004] CN113620988A discloses a formula of a composite rubber antioxidant, which is a reactive antioxidant synthesized from p-phenylenediamine as a basic raw material. This type of antioxidant contains both active groups that can react with rubber macromolecules and groups that have the function of inhibiting rubber aging, and has the characteristics of non-migration, non-volatility and non-extraction.

[0005] CN112980217A proposes a method for modifying a graphene oxide (GO)-silicon dioxide (SiO2) composite filler to solve the problem of poor dispersion and easy agglomeration of GO and SiO2 in rubber. At the same time, the composite filler is endowed with anti-aging properties by modifying GO. However, a large amount of the composite filler added will affect the vulcanization performance of the rubber.

[0006] In the prior art, antioxidants have weak antioxidant capacity and migrate in the rubber network as the environment changes during use, causing the rubber to "frost". Summary of the invention

[0007] The purpose of the present invention is to overcome the problems of the prior art that the rubber antioxidant is easy to volatilize, easy to migrate, has poor dispersibility in rubber and poor extraction resistance, and to provide a composite material and a preparation method and application thereof, as well as rubber.

[0008] In order to achieve the above object, the present invention provides a composite material in a first aspect, wherein the composite material comprises: a modified inorganic filler and a structure A1 represented by formula (1) connected to the surface of the modified inorganic filler,

[0009]

[0010] Wherein, R is selected from H or Wherein R1 is selected from H or C1-C6 alkyl, R' is selected from H, C1-C 10 alkyl, wherein R2 is selected from C1-C6 alkylene or C1-C6 alkylene ether, R3 is selected from C1-C6 alkylene, and R4 is selected from C1-C 12 alkyl;

[0011] R" does not exist or is selected from C1-C 20 oxygen-containing groups.

[0012] A second aspect of the present invention provides a method for preparing a composite material, comprising the following steps:

[0013] (1) subjecting an inorganic filler to a first reaction with a coupling agent to obtain a first product;

[0014] (2) Under the action of a catalyst, subjecting the first product to a second reaction with the compound c represented by formula (2) to obtain the composite material, wherein the coupling agent is a compound containing an epoxy group;

[0015] Or include the following steps:

[0016] (1) subjecting an inorganic filler to a first reaction with a coupling agent to obtain a first product;

[0017] (2) subjecting the compound c represented by formula (2) to an addition reaction with an epoxy compound to obtain a second product;

[0018] (3) Under the action of a catalyst, subjecting the first product and the second product to a third reaction to obtain the composite material; wherein the coupling agent is a compound that does not contain an epoxy group;

[0019]

[0020] The definitions of R and R' are the same as those described in the first aspect.

[0021] The third aspect of the present invention provides a composite material obtained by the preparation method.

[0022] A fourth aspect of the present invention provides a use of the composite material as an antioxidant in rubber.

[0023] A fifth aspect of the present invention provides a rubber, wherein the rubber comprises raw rubber and the composite material.

[0024] Through the above technical scheme, the present invention provides a composite material used as an antioxidant in rubber, and by introducing a coupling structure M and a group shown in formula (1) into the composite material, wherein the coupling structure M can introduce an oxygen-containing or sulfur-containing group, and the group shown in formula (1) can also introduce an oxygen-containing or sulfur-containing group, the obtained composite antioxidant has good heat-oxidative aging strength, excellent migration resistance, and better compatibility between the antioxidant with aromatic group and the rubber with aromatic group; the composite material as a rubber antioxidant has the medium- and long-term protective performance of traditional antioxidants, and at the same time has the characteristic of migration resistance; the preparation method of the rubber antioxidant has the advantages of simple process and high product yield; in addition, the rubber antioxidant has good dispersibility in rubber. DETAILED DESCRIPTION

[0025] The endpoints and any values ​​of the ranges disclosed in this article are not limited to the precise ranges or values, and these ranges or values ​​should be understood to include values ​​close to these ranges or values. For numerical ranges, the endpoint values ​​of each range, the endpoint values ​​of each range and the individual point values, and the individual point values ​​can be combined with each other to obtain one or more new numerical ranges, which should be considered as specifically disclosed in this article.

[0026] A first aspect of the present invention provides a composite material, wherein the composite material comprises: a modified inorganic filler and a structure A1 represented by formula (1) connected to the surface of the modified inorganic filler,

[0027]

[0028] Wherein, R is selected from H or Wherein R1 is selected from H or C1-C6 alkyl, R' is selected from H, C1-C 10 alkyl, wherein R2 is selected from C1-C6 alkylene or C1-C6 alkylene ether, R3 is selected from C1-C6 alkylene, and R4 is selected from C1-C 12 alkyl;

[0029] R" does not exist or is selected from C1-C 20 oxygen-containing groups.

[0030] In the present invention, by introducing a coupling structure M and a structure A1 shown in formula (1) into the surface of the inorganic filler in the composite material, wherein the coupling structure M can introduce an oxygen-containing or sulfur-containing group and play a role in connecting the surface of the inorganic particle and the group, and the structure A1 can also introduce an oxygen-containing or sulfur-containing group, thereby coating or modifying the inorganic particles, the obtained composite material has good thermal oxygen aging strength and excellent migration resistance as an antioxidant.

[0031] In some embodiments of the present invention, R" is selected from

[0032] R5 is absent or selected from wherein R6 is selected from C1-C6 alkylene ethers, wherein R7 is selected from C1-C 15 Alkyl ether.

[0033] In some specific embodiments of the present invention, the modified inorganic filler includes an inorganic filler and a coupling structure M, wherein the coupling structure M is attached to the surface of the inorganic filler and connected to the structure A1.

[0034] In some specific embodiments of the present invention, the inorganic filler is selected from one or more of carbon black N330, carbon black N660 and white carbon black.

[0035] In some specific embodiments of the present invention, the coupling structure M is a residue selected from one or more of γ-aminopropyltriethoxysilane (KH550), γ-glycidyloxypropyltrimethoxysilane (KH560), bis-[γ-(triethoxysilyl)propyl]-tetrasulfide (Si-69), (3-ethoxysilylpropyl)-disulfide (Si-75) and 3-octanoylthiopropyltriethoxysilane (Si-777).

[0036] In some specific embodiments of the present invention, the coupling structure M can be selected from

[0037] The coupled structure M is bonded to the O atom in R" in structure A1 via the Si atom in M, and the coupled structure M is bonded to the N atom in structure A1 via the C atom in M.

[0038] In the present invention, the coupling structure M includes but is not limited to the above structure.

[0039] In some specific embodiments of the present invention, in the composite material, the weight ratio of the modified inorganic filler to structure A1 is 10:(0.2-2).

[0040] In some specific embodiments of the present invention, the modified inorganic filler contains 0.001-0.002 mol of the coupling structure M relative to 10 g.

[0041] In some specific embodiments of the present invention, the composite material can be selected from at least one of the following structures (schematic structures):

[0042] Composite material-1:

[0043] Composite material-2:

[0044] Composite material-3:

[0045]

[0046] Composite material-4:

[0047]

[0048] Composite material-5:

[0049]

[0050] Composite material-6:

[0051] Composite material-7:

[0052] In the present invention, the hydroxyl group formed by the epoxy group is not limited to reacting with the Si-O-C2H5 group at a specific position in the coupling agent, that is, it can react with the Si-O-C2H5 group at any position in the coupling agent; the composite material structure includes but is not limited to the above structure.

[0053] In the present invention, the composition and structure of the composite material can be determined by nuclear magnetic resonance, infrared, GPC, elemental analysis, etc., or by preparing and feeding.

[0054] A second aspect of the present invention provides a method for preparing a composite material, comprising the following steps:

[0055] (1) subjecting an inorganic filler to a first reaction with a coupling agent to obtain a first product;

[0056] (2) Under the action of a catalyst, subjecting the first product to a second reaction with the compound c represented by formula (2) to obtain the composite material, wherein the coupling agent is a compound containing an epoxy group;

[0057] Or include the following steps:

[0058] (1) subjecting an inorganic filler to a first reaction with a coupling agent to obtain a first product;

[0059] (2) subjecting the compound c represented by formula (2) to an addition reaction with an epoxy compound to obtain a second product;

[0060] (3) Under the action of a catalyst, subjecting the first product and the second product to a third reaction to obtain the composite material; wherein the coupling agent is a compound that does not contain an epoxy group;

[0061]

[0062] The definitions of R and R' are the same as those described in the first aspect.

[0063] In some specific embodiments of the present invention, the compound c is selected from one or more of aniline, p-phenylenediamine, 4-aminodiphenylamine (RT base), N-isopropyl-N'-phenyl-p-phenylenediamine (IPPD), N-(1,3-dimethylbutyl)-N'-phenyl-p-phenylenediamine (6PPD), N-(1,4-dimethylpentyl)-N'-phenyl-p-phenylenediamine (7PPD), N,N'-bis(1,4-dimethylpentyl)-p-phenylenediamine (77PD), N-(1-methylheptyl)-N'-phenyl-p-phenylenediamine (8PPD), N,N'-di-sec-butyl-p-phenylenediamine (44PD), 1-(ethylthio)-3-(phenylamino)-2-propanol (CAS: 101684-31-5) and 1-(octylthio)-3-(phenylamino)-2-propanol (CAS: 101684-37-1).

[0064] In some specific embodiments of the present invention, the coupling agent is selected from one or more of γ-aminopropyltriethoxysilane (KH550), γ-glycidyloxypropyltrimethoxysilane (KH560), bis-[γ-(triethoxysilyl)propyl]-tetrasulfide (Si-69), (3-ethoxysilylpropyl)-disulfide (Si-75) and 3-octanoylthiopropyltriethoxysilane (Si-777). The coupling agent in the present invention is attached to the surface of the inorganic filler and is used to bond the inorganic filler to the organic part (structure A1 in the first aspect), and the coupling agent provides the coupling structure M in the first aspect.

[0065] In some specific embodiments of the present invention, the inorganic filler is selected from one or more of carbon black N330, carbon black N660 and white carbon black.

[0066] In some specific embodiments of the present invention, the epoxy compound is selected from one or more of methacrylate glycidyl ether, allyl glycidyl ether, 4-hydroxybutyl acrylate glycidyl ether, lauryl glycidyl ether and diglycidyl ether.

[0067] In the present invention, when the coupling agent is a compound containing an epoxy group, the compound c provides the structure A1 in the first aspect; when the coupling agent is a compound not containing an epoxy group, the second product obtained by the reaction of the epoxy compound and the compound c provides the structure A1 in the first aspect.

[0068] In some specific embodiments of the present invention, in step (1), before the inorganic filler undergoes the first reaction, the inorganic filler needs to be placed in a dilute hydrochloric acid solution and allowed to stand for 24-72 hours to acid-wash the inorganic filler.

[0069] In some specific embodiments of the present invention, the catalyst is selected from one or more of formic acid, salicylic acid and dibutyltin dilaurate.

[0070] In some specific embodiments of the present invention, the first reaction is carried out under solvent conditions, wherein the solvent is selected from one or more of benzene, toluene, xylene, chloroform, methanol, tetrahydrofuran and acetone.

[0071] In some specific embodiments of the present invention, the first reaction temperature is 10-40° C., and the first reaction time is 24-48 h.

[0072] In some specific embodiments of the present invention, the second reaction temperature is 80-150° C., and the second reaction time is 3-15 h.

[0073] In some specific embodiments of the present invention, the addition reaction temperature is 80-150° C., and the addition reaction time is 3-15 h.

[0074] In some specific embodiments of the present invention, the third reaction temperature is 80-190° C., and the second reaction time is 3-15 h.

[0075] In some specific embodiments of the present invention, in step (1), the inorganic filler is 10-30 parts by weight. In the present invention, since the inorganic filler is immersed in the coupling agent solution during the reaction process, the coupling agent is excessive. The feeding amount is not particularly limited herein. Relative to 10g of the modified inorganic filler, 0.001-0.002mol of coupling agent can be loaded.

[0076] In some specific embodiments of the present invention, when the coupling agent is a compound containing an epoxy group, in step (2), relative to 5-15 g of the first product, the compound c is 0.01-0.5 mol.

[0077] In some specific embodiments of the present invention, when the coupling agent is a compound without epoxy group, relative to the first product, it is 5-15 g, the compound c is 0.01-0.5 mol, and the epoxy compound is 0.01-0.5 mol.

[0078] In the present invention, the composition and structure of the composite material can be determined by nuclear magnetic resonance, infrared, GPC, elemental analysis, etc., or by preparing and feeding.

[0079] The third aspect of the present invention provides a composite material obtained by the preparation method.

[0080] A fourth aspect of the present invention provides a use of the composite material as an antioxidant in rubber.

[0081] A fifth aspect of the present invention provides a rubber, wherein the rubber comprises raw rubber and the composite material.

[0082] In some specific embodiments of the present invention, the compound is added to the rubber in an amount of 2-3 wt % of the raw rubber.

[0083] In some specific embodiments of the present invention, the mobility of the compound in the rubber is 1-3.5%.

[0084] The present invention will be described in detail below through examples.

[0085] In the following examples and comparative examples, if no specific conditions are specified, the reaction is carried out under conventional conditions or conditions recommended by the manufacturer. The reagents or instruments used without indicating the manufacturer are all conventional products that can be obtained through commercial channels. The composition and structure of the composite materials prepared in the following examples are determined by preparing the feed (after the reaction of the example is completed, the feed is basically reacted completely).

[0086] Example 1

[0087] First, 20g of carbon black N330 was placed in a dilute hydrochloric acid solution and allowed to stand for 48h, washed with water until neutral, immersed in a 3wt% coupling agent (KH550) aqueous solution and allowed to stand for 24h, washed with water three times, and then vacuum dried at 80°C for 8h to obtain a filler carrier with a connection group on the surface; 0.01mol of p-phenylenediamine was dissolved in 50mL of chloroform and mixed with 10g of the treated filler carrier, reacted at 80°C for 10h under acidic conditions, and the reaction mixture was transferred to a rotary evaporator to remove the solvent and then cooled to room temperature to obtain a composite material A1;

[0088] Wherein, the weight ratio of the modified inorganic filler to structure A1 is 10:0.54;

[0089] The schematic structure of composite material A1 is as follows:

[0090] Example 2

[0091] First, 20g of carbon black N660 was placed in a dilute hydrochloric acid solution and allowed to stand for 48h, washed with water until neutral, immersed in a coupling agent (KH560) aqueous solution with a mass fraction of 3wt% and allowed to stand for 24h, washed with water three times, and vacuum dried at 80°C for 8h to obtain a filler carrier with a connection group on the surface; 0.01mol of RT base was dissolved in 50mL of acetone and reacted with 0.01mol of glycidyl methacrylate at 105°C for 2h, the obtained product was mixed with 10g of the treated filler carrier, reacted at 80°C for 10h under acidic conditions, the reaction mixture was transferred to a rotary evaporator to remove the solvent, and then cooled to room temperature to obtain a composite material A2;

[0092] Wherein, the weight ratio of the modified inorganic filler to structure A1 is 10:0.54;

[0093] The schematic structure of composite material A2 is:

[0094]

[0095] Example 3

[0096] First, 20g of white carbon black was placed in a dilute hydrochloric acid solution and allowed to stand for 60h, washed with water until neutral, and then immersed in a coupling agent (Si-69) aqueous solution with a mass fraction of 3wt% and allowed to stand for 24h. After washing with water three times, the mixture was vacuum dried at 80°C for 8h to obtain a filler carrier with a connection group on the surface; 0.01mol of IPPD was dissolved in 50mL of acetone and reacted with 0.01mol of glycidyl methacrylate at 105°C for 2h, and the obtained product was mixed with 10g of the treated filler carrier, and reacted at 80°C for 10h under acidic conditions. The reaction mixture was transferred to a rotary evaporator to remove the solvent and then cooled to room temperature to obtain a composite material A3;

[0097] Wherein, the weight ratio of the modified inorganic filler to structure A1 is 10:0.92;

[0098] The schematic structure of composite material A3 is as follows:

[0099]

[0100] Example 4

[0101] First, 20g of carbon black N330 was placed in a dilute hydrochloric acid solution and allowed to stand for 48h, washed with water until neutral, immersed in a 3wt% coupling agent (KH550) aqueous solution and allowed to stand for 24h, washed with water three times, and vacuum dried at 80°C for 8h to obtain a filler carrier with a connection group on the surface; 0.01mol of 6PPD was dissolved in 50mL of acetone and reacted with 0.01mol of glycidyl methacrylate at 105°C for 2h, the obtained product was mixed with 10g of the treated filler carrier, reacted at 80°C for 10h under acidic conditions, the reaction mixture was transferred to a rotary evaporator to remove the solvent, and then cooled to room temperature to obtain a composite material A4;

[0102] Wherein, the weight ratio of the modified inorganic filler to structure A1 is 10:1.34;

[0103] The schematic structure of composite material A4 is as follows:

[0104]

[0105] Example 5

[0106] First, 20g of white carbon black was placed in a dilute hydrochloric acid solution and allowed to stand for 60h, washed with water until neutral, immersed in a coupling agent (Si-69) aqueous solution with a mass fraction of 3wt% and allowed to stand for 24h, washed with water three times, and vacuum dried at 80°C for 8h to obtain a filler carrier with a connection group on the surface; 0.01mol of 44PD was dissolved in 50mL of acetone and reacted with 0.01mol of glycidyl methacrylate at 105°C for 2h, the obtained product was mixed with 10g of the treated filler carrier, reacted at 80°C for 10h under acidic conditions, the reaction mixture was transferred to a rotary evaporator to remove the solvent, and then cooled to room temperature to obtain the composite material A5;

[0107] Wherein, the weight ratio of the modified inorganic filler to structure A1 is 10:1.1;

[0108] The schematic structure of composite material A5 is as follows:

[0109]

[0110] Example 6

[0111] First, 20g of carbon black N330 was placed in a dilute hydrochloric acid solution and allowed to stand for 48h, washed with water until neutral, immersed in a coupling agent (KH550) aqueous solution with a mass fraction of 3wt% and allowed to stand for 24h, washed with water three times, and vacuum dried at 80°C for 8h to obtain a filler carrier with a connection group on the surface; 0.01mol of 77PD was dissolved in 50mL of acetone and reacted with 0.01mol of glycidyl methacrylate at 105°C for 2h, the obtained product was mixed with 10g of the treated filler carrier, reacted at 80°C for 10h under acidic conditions, the reaction mixture was transferred to a rotary evaporator to remove the solvent, and then cooled to room temperature to obtain the composite material A6;

[0112] Wherein, the weight ratio of the modified inorganic filler to structure A1 is 10:1.52;

[0113] The schematic structure of the composite material A6 is as follows:

[0114] Example 7

[0115] First, 20g of carbon black N660 was placed in a dilute hydrochloric acid solution and allowed to stand for 48h, washed with water until neutral, immersed in a 3wt% coupling agent (KH560) aqueous solution and allowed to stand for 24h, washed with water three times, and then vacuum dried at 80°C for 8h to obtain a filler carrier with a connection group on the surface; 0.01mol of 1-(octylthio)-3-(phenylamino)-2-propanol was dissolved in 50mL of acetone and mixed with 10g of the treated filler carrier, reacted at 80°C for 10h under acidic conditions, and the reaction mixture was transferred to a rotary evaporator to remove the solvent and then cooled to room temperature to obtain a composite material A7;

[0116] Wherein, the weight ratio of the modified inorganic filler to structure A1 is 10:1.48;

[0117] The schematic structure of the composite material A7 is as follows:

[0118]

[0119] Test Case

[0120] 100 parts by weight of styrene-butadiene rubber, 5 parts by weight of zinc oxide, 2 parts by weight of stearic acid, 45 parts by weight of carbon black N330, 1.5 parts by weight of accelerator, 2.5 parts by weight of insoluble sulfur and 2 parts by weight of composite materials A1-A7 obtained in Examples 1-7 were mixed, kneaded and vulcanized to obtain vulcanized rubbers B1-B7. The standard dumbbell-shaped films were cut by a slicer and subjected to thermal oxidation aging test and migration resistance test respectively.

[0121] Test comparative example 1: 100 parts by weight of styrene-butadiene rubber, 5 parts by weight of zinc oxide, 2 parts by weight of stearic acid, 45 parts by weight of carbon black N660, 1.5 parts by weight of accelerator, 2.5 parts by weight of insoluble sulfur and 2 parts by weight of antioxidant IPPD were mixed and kneaded, and vulcanized to obtain vulcanized rubber D1, and thermal oxidation aging test and migration resistance test were respectively carried out.

[0122] Test comparative example 2: 100 parts by weight of styrene-butadiene rubber, 5 parts by weight of zinc oxide, 2 parts by weight of stearic acid, 45 parts by weight of carbon black N660, 1.5 parts by weight of accelerator, 2.5 parts by weight of insoluble sulfur and 2 parts by weight of antioxidant 6PPD were mixed and kneaded, and vulcanized to obtain vulcanized rubber D2, and thermal oxidation aging test and migration resistance test were respectively carried out.

[0123] In the thermal oxygen aging experiment, the aging temperature was set at 100°C, and the test sample was aged for 3 days. The retention rate of the tensile strength of the material after 7 days was taken as the anti-aging efficiency, and the retention rate (%) = parameter after aging / parameter before aging × 100%.

[0124] The migration resistance test includes water extraction resistance and migration test. For water extraction resistance, two pieces of film weighing about 5g were completely immersed in 100mL deionized water. After soaking at room temperature for 14 days, the water was evaporated and made into 10mL methanol solution. The antioxidant content in the solution was detected by high performance liquid chromatography. For the migration test, the film was contacted with a blank film without antioxidant at a pressure of 1MPa and 90℃ for 300min. Acetone was used as a solvent to extract the blank film and test the antioxidant content in acetone. The results are shown in Table 1.

[0125] Table 1

[0126]

[0127] It can be seen from the results in Table 1 that the composite antioxidant obtained by Examples 1-7 of the present invention is used for performance testing. The tensile strength retention rate after 3 days and 7 days of thermal oxidative aging is high, and the water extraction rate and migration rate are only 1 / 10 of those in the comparative example. The antioxidant obtained by the technical solution of the present invention has good thermal oxidative aging strength and excellent migration resistance.

[0128] The preferred embodiments of the present invention are described in detail above, but the present invention is not limited thereto. Within the technical concept of the present invention, the technical solution of the present invention can be subjected to a variety of simple modifications, including the combination of various technical features in any other suitable manner, and these simple modifications and combinations should also be regarded as the contents disclosed by the present invention and belong to the protection scope of the present invention.

Claims

1. A composite material, characterized in that: The composite material comprises: a modified inorganic filler and a structure A1 represented by formula (1) connected to the surface of the modified inorganic filler, Wherein, R is selected from H or wherein R1 is selected from H or C1-C6 alkyl, R' is selected from H, C1-C 10 alkyl, wherein R2 is selected from C1-C6 alkylene or C1-C6 alkylene ether, R3 is selected from C1-C6 alkylene, and R4 is selected from C1-C 12 alkyl; R" does not exist or is selected from C1-C 20 oxygen-containing groups.

2. The composite material according to claim 1, characterized in that R" is selected from R5 is absent or selected from wherein R6 is selected from C1-C6 alkylene ethers, wherein R7 is selected from C1-C 15 Alkyl ether.

3. The composite material according to claim 1 or 2, characterized in that: The modified inorganic filler comprises an inorganic filler and a coupling structure M, wherein the coupling structure M is attached to the surface of the inorganic filler and connected to the structure A1; Preferably, the inorganic filler is selected from one or more of carbon black N330, carbon black N660 and white carbon black.

4. The composite material according to any one of claims 1 to 3, characterized in that The coupling structure M is a residue selected from one or more of γ-aminopropyltriethoxysilane, γ-glycidyloxypropyltrimethoxysilane, bis-[γ-(triethoxysilyl)propyl]-tetrasulfide, (3-ethoxysilylpropyl)-disulfide and 3-octanoylthiopropyltriethoxysilane; Preferably, in the composite material, the weight ratio of the modified inorganic filler to structure A1 is 10:(0.2-2).

5. A method for preparing a composite material, characterized in that: The steps include: (1) subjecting an inorganic filler to a first reaction with a coupling agent to obtain a first product; (2) Under the action of a catalyst, subjecting the first product to a second reaction with the compound c represented by formula (2) to obtain the composite material, wherein the coupling agent is a compound containing an epoxy group; Or include the following steps: (1) subjecting an inorganic filler to a first reaction with a coupling agent to obtain a first product; (2) subjecting the compound c represented by formula (2) to an addition reaction with an epoxy compound to obtain a second product; (3) Under the action of a catalyst, subjecting the first product and the second product to a third reaction to obtain the composite material; wherein the coupling agent is a compound that does not contain an epoxy group; The definitions of R and R' are the same as those in any one of claims 1 to 4.

6. The preparation method according to claim 5, characterized in that: The compound c is selected from one or more of aniline, p-phenylenediamine, 4-aminodiphenylamine, N-isopropyl-N'-phenyl-p-phenylenediamine, N-(1,3-dimethylbutyl)-N'-phenyl-p-phenylenediamine, N-(1,4-dimethylpentyl)-N'-phenyl-p-phenylenediamine, N,N'-bis(1,4-dimethylpentyl)-p-phenylenediamine, N-(1-methylheptyl)-N'-phenyl-p-phenylenediamine, N,N'-di-sec-butyl-p-phenylenediamine, 1-(ethylthio)-3-(phenylamino)-2-propanol and 1-(octylthio)-3-(phenylamino)-2-propanol; Preferably, the coupling agent is selected from one or more of γ-aminopropyltriethoxysilane, γ-glycidyloxypropyltrimethoxysilane, bis-[γ-(triethoxysilyl)propyl]-tetrasulfide, (3-ethoxysilylpropyl)-disulfide and 3-octanoylthiopropyltriethoxysilane; Preferably, the inorganic filler is selected from one or more of carbon black N330, carbon black N660 and white carbon black; Preferably, the epoxy compound is selected from one or more of methacrylate glycidyl ether, allyl glycidyl ether, 4-hydroxybutyl acrylate glycidyl ether, lauryl glycidyl ether and diglycidyl ether; Preferably, in step (1), before the inorganic filler undergoes the first reaction, the inorganic filler needs to be placed in a dilute hydrochloric acid solution and allowed to stand for 24-72 hours; Preferably, the catalyst is selected from one or more of formic acid, salicylic acid and dibutyltin dilaurate.

7. The preparation method according to any one of claims 5 or 6, characterized in that: The first reaction temperature is 10-40°C, and the first reaction time is 24-48h; Preferably, the second reaction temperature is 80-190°C, and the second reaction time is 3-15h; Preferably, the addition reaction temperature is 80-150°C, and the addition reaction time is 3-15h; Preferably, the third reaction temperature is 80-190° C., and the second reaction time is 3-15 h.

8. The preparation method according to any one of claims 5 to 7, characterized in that: In step (1), the inorganic filler is 10-30 parts by weight; Preferably, when the coupling agent is a compound containing an epoxy group, in step (2), the compound c is 0.01-0.5 mol relative to 5-15 g of the first product; Preferably, when the coupling agent is a compound without epoxy group, relative to the first product, the amount is 5-15 g, the amount of compound c is 0.01-0.5 mol, and the amount of epoxy compound is 0.01-0.5 mol.

9. The composite material obtained by the preparation method according to any one of claims 5 to 8.

10. Use of the composite material according to any one of claims 1 to 4 and 9 as an antioxidant in rubber.

11. A rubber, characterized in that: The rubber comprises raw rubber and the composite material according to any one of claims 1 to 4 and 9.

12. The rubber according to claim 11, characterized in that In the rubber, the composite material is added in an amount of 2-3 wt% of the raw rubber; Preferably, the mobility of the composite material in the rubber is 1-3.5%.

Citation Information

Patent Citations

  • Preparation method of modified GO-SiO2 composite filler and application of modified GO-SiO2 composite filler in rubber

    CN112980217A

  • Composite rubber anti-aging agent and preparation process thereof

    CN113620988A

  • Silane coupling agent and preparation method thereof

    CN102584886A

  • Hybrid filler load type anti-aging agent, and preparation method and application thereof

    CN107189102A

  • Functional mesoporous silicon dioxide nanoparticles with effect of resisting ageing and preparing method and application of functional mesoporous silicon dioxide nanoparticles

    CN107337809A